Which Internal Medicine Clerkship Characteristics Are Associated With Students' Performance on the NBME Medicine Subject Exam? A Multi-Institutional Analysis - Fitz, Matthew M; Adams, William; Haist, Steven A; Hauer, Karen E; Ross, Linette P; Raff, Amanda; Agarwal, Gauri; Vu, T Robert; Appelbaum, Jonathan; Lang, Valerie J; Miller, Chad; Grum, Cyril (Academic medicine, 2020)
To identify which internal medicine clerkship characteristics may relate to NBME Medicine Subject Examination scores, given the growing trend toward earlier clerkship start dates. The authors used linear mixed effects models (univariable and multivariable) to determine associations between medicine exam performance and clerkship characteristics (longitudinal status, clerkship length, academic start month, ambulatory clinical experience, presence of a study day, involvement in a combined clerkship, preclinical curriculum type, medicine exam timing). Additional covariates included number of NBME clinical subject exams used, number of didactic hours, use of a criterion score for passing the medicine exam, whether medicine exam performance was used to designate clerkship honors, and United States Medical Licensing Examination Step 1 performance. The sample included 24,542 examinees from 62 medical schools spanning 3 academic years (2011-2014). The multivariable analysis found no significant association between clerkship length and medicine exam performance (all pairwise P > .05). However, a small number of examinees beginning their academic term in January scored marginally lower than those starting in July (P < .001). Conversely, examinees scored higher on the medicine exam later in the academic year (all pairwise P < .001). Examinees from schools that used a criterion score for passing the medicine exam also scored higher than those at schools that did not (P < .05). Step 1 performance remained positively associated with medicine exam performance even after controlling for all other variables in the model (P < .001). In this sample, the authors found no association between many clerkship variables and medicine exam performance. Instead, Step 1 performance was the most powerful predictor of medicine exam performance. These findings suggest that medicine exam performance reflects the overall medical knowledge students accrue during their education rather than any specific internal medicine clerkship characteristics.